2021
DOI: 10.48550/arxiv.2104.02554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delayed buckling of spherical shells due to viscoelastic knockdown of the critical load

Lucia Stein-Montalvo,
Douglas P. Holmes,
Gwennou Coupier

Abstract: We performed dynamic pressure buckling experiments on defect-seeded spherical shells made of a common silicone elastomer. Unlike in quasi-static experiments, shells buckled at ostensibly subcritical pressures (i.e. below the experimentally-determined load at which buckling occurs elastically), often following a significant time delay. While emphasizing the close connections to elastic shell buckling, we rely on viscoelasticity to explain our observations. In particular, we demonstrate that the lower critical l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Yet, the opposite can also be true. Stein-Moldavo et al recently showed that the buckling pressure of spherical shells could also drop due to viscoelastic effects [44]. When a negative pressure was kept stable just below the elastic buckling limit, a viscoelastic shell would still buckle after relaxation.…”
Section: Using Viscoelas�citymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the opposite can also be true. Stein-Moldavo et al recently showed that the buckling pressure of spherical shells could also drop due to viscoelastic effects [44]. When a negative pressure was kept stable just below the elastic buckling limit, a viscoelastic shell would still buckle after relaxation.…”
Section: Using Viscoelas�citymentioning
confidence: 99%
“…As such, dissipative vibration transmissions has been studied extensively in acoustic metamaterials featuring wave propagation and band gap structures [21,22,23,24,25,26,27,28,29,30] as well vibration and shock control [31,32,33,34,35,36]. However, although the effect of the constitutive materials' dissipation on mechanical instabilities has been well studied [37,38,39,40,41,42,43,44], the role of dissipation in the instabilities that underpin the extreme mechanics of mechanical metamaterials remains poorly understood (Fig 1). Yet, there is growing evidence that dissipation can play a key role in the response of mechanical metamaterials that are based on buckling [45,46].…”
Section: Introductionmentioning
confidence: 99%